Marketing Strategies in Increasing Turnover and Product Quality of Msme KSM Berkah - Nuryadi, Nuryadi; Zaman, Komarun; Utomo, Priyo; Arifin, Syamsul; Adhitya Pratama, Devangga Putra (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Srikandi Tempe Chips is engaged in the small food industry at this time, Srikandi Tempe Chips companies are competing in very tight competition in retaining customers. So, companies must really consider marketing strategies in order to improve product quality. The type of research used in this study is a qualitative approach, which aims to find out a good marketing strategy, which is associated with the strengths, weaknesses, opportunities and threats owned by UMKM KSM Berkah in increasing turnover and product quality. From the results of this study that has been carried out, it shows that Srikandi Tempe Chips are successful in implementing marketing strategies using SWOT analysis.